Causes of Multi Years Contract Project Delay - Faslan Syam Sajiah (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2020)
Delay in construction projects is considered one of the most common problems, causing a multitude of negative effects on the project and its participating parties. Delays can cause losses to the economy, cost overruns, disputes, arbitration, abandonment, and poor quality of finished project. This paper aims to identify the main causes of delay in multi years infrastructure projects in Indonesia. Based on secondary data from documents for Proposals and Completion of Extension of Multi-Year Contract Approval in the FY 2018 and 2019 which are processed at the Ministry of Finance, 19 factors that caused the delay were identified. The importance indexes measured and ranked the level of importance of the delay factors. The main five causes of time delays included land acquisition problem, design change, failed tender, inadequate site investigation, and shortage of construction materials. Majority of the cause is attributed to Ministry/Institution as project owner. The results can help project owners, contractors, and consultants in understanding the reasons for the delay, so that each party, especially the Ministry/Agency as the project owner, can eliminate or minimize these causes.